Investment Activities and Performance of Gigamon Companies Around the World - Ochilov Bobur Bakhtiyarovich (Peerian Journals Publishing, 2022)
This article analyzes the financial performance of the world’s gigamon corporations, the independent stock market as a result of the healthy investment climate in developed countries, the improvement of living standards, financial and investment stability, the country’s annual production capacity, at the same time, it is written about the growth of the country’s GDP as a result of the export potential of high-capitalized companies, how a single company can benefit the entire country
Keywords: Gigamon companies; capitalization,; stocks; investors